Application of Product Design, Design of Digital Promotion Tools and Design of On-Line Marketing Media for MSMEs Pupuk Bokashi in Getasan District Semarang Regency - Nurkhayati, Isnaini; Sulistiyani, Endang; Azizah, Azizah; Nugroho, Jati (Society : Jurnal Pengabdian Masyarakat, 2024)
Community service aims to help provide solutions to problems in the fields of production, promotion and marketing faced by MSMEs of Pupuk Bokashi,Getasan District, Semarang Regency.Community Service is carried out in order to improve product quality, expand marketing areas, and increase the income of partner MSMEs.The problem faced by MSME partners is the lack of ability of MSME actors to master science and technology, think creatively and innovate in designing products, product packaging, designing promotional tools and marketing their products, so that marketing area coverage is still limited and sales turnover is still low. The solution will be provided, namely Providing training and assistance in implementing attractive product and packaging designs, creating digital promotional tool designs and creating on-line Marketing Media designs to expand marketing areas and increase sales turnover, creating new ideas from online media and assistance in making accounts on Social Media and selling accounts on the Marketplace. The method used is to provide training and assistance in making product and packaging designs, promotional tool designs and online marketing media designs.Application of technology in creating product designs, product packaging, promotional tools and online marketing media will affect product quality, expansion of marketing areas, increase in sales turnover and increase in MSME profits. Changes in marketing behavior from conventional to online marketing must be balanced with the ability of MSME players to design products to make them more attractive, design effective digital promotional tools so that products are easily recognized and use online marketing technology to expand marketing areas. It is hoped that online marketing media will be an effective choice for MSME players so they can reach a wider marketing area, increase sales turnover, so that it will have an impact on increasing the profit level of Pupuk Bokashi MSMEs, Getasan District.